Student enrolment system for PTPL college - Azizah, Jamel; Fatwa Syazwani, Mohamad; Liza, Maten (University Malaysia Sarawak, UNIMAS., 2004)
Year by year, the world fast growing with modernization of Information Technology, many implementations of which has been brought up in processing data. The new technologies have brought up the environment to develop new system each year. People get established knowledge and know more in using any computerized system. The implementation of Student Enrollment System for PTPL College is based on Visual Basic interface that integrates with Microsoft Access database platform. It is developed to meet the organization's requirements.